Meninjau Pengaruh Transformasi Digital pada Perancangan dan Dunia Virtual - Raisha Gebrina Razky; Sarvina Fitri Rizky; Sylvia Agustina (Jurnal RAUT, 2022)
This study discusses digital design through Virtual World, a computer algorithm formed to create a "new world" or add a 2D / 3D reality and even audio and video to the real world. There are several kinds of virtual worlds that have been developed. The virtual world consists of virtual reality, augmented reality, mixed reality. The Virtual World is also closely related to architecture. Information Technology has an important role in the advancement and development of presentations in architecture. The resulting role has a considerable impact. One of them is the use of Virtual Reality (VR) in architectural presentations. VR is an achievement that makes it easy to communicate design results. Therefore, this study will discuss how the virtual world is the latest breakthrough and is enough to influence developments in the architectural world today and can facilitate the lives of architects and the public.